2007
DOI: 10.1177/154193120705101918
|View full text |Cite
|
Sign up to set email alerts
|

The Control Strategy for Degrees of Freedom in Remote Prehension with a Tool

Abstract: Constructing movement couplings is essential for decreasing degrees-of-freedom for a compound movement that requires coordination over a multiple segments. Angular movements of joints in the upper limbs are examined, the pattern of movement couplings between prehension performed with the hands (natural prehension) and with a simple grasper held in the hands (remote prehension). In remote prehension, the shoulder and elbow joint are tightly associated with a clear in-phase joint to joint movement; the elbow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For example, articulating instruments would facilitate intracorporeal suturing, especially in difficult positions such as the anterior abdominal wall of the deep pelvis. However, such potential advantages may be offset by the increased complexity of the instrument, which may make it harder to predict the movement outcome and more difficult to build movement coordination between the hand and the tool [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, articulating instruments would facilitate intracorporeal suturing, especially in difficult positions such as the anterior abdominal wall of the deep pelvis. However, such potential advantages may be offset by the increased complexity of the instrument, which may make it harder to predict the movement outcome and more difficult to build movement coordination between the hand and the tool [6].…”
Section: Introductionmentioning
confidence: 99%
“…The first type of instrument with intracorporeal DOF has a simple mechanical control of intracorporeal DOF, such as a knee joint between the handle and the shaft. However they do not seem to improve dexterity because of the complexity of the control mode [4]. A research axis to overcome both ergonomic issues and a potentially difficult control mode is the creation of robotized instruments.…”
mentioning
confidence: 99%
“…However, it is known that surgeons need to go through several learning phases, including recalibrating the motor plan by integrating the mechanical properties of the tool into the motor system, and generating movements with adjustments to the hands to ensure the outcome from the endpoints of tools to fulfill a task goal. 6,9 The tool adaption process of a human operator with a tool requires practice time. Once the adaptation process with a tool is completed, movement control with a tool becomes automatic.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on the human tool interaction has revealed that the mechanical complexity of a tool can modify the movement coordination built among motor segments of a human operator's upper limb. 9 Compared with instruments for open procedures, instruments designed for performing laparoscopic, single-port access, and endoscopic procedures are more complicated with an increasing number of hinges and degrees of freedom. 2,5 The first goal of this project was to carefully assess the influence of the tool complexity on surgeons' performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation